2018
DOI: 10.1016/j.ces.2018.06.045
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative comparison of in-line coating thickness distributions obtained from a pharmaceutical tablet mixing process using discrete element method and terahertz pulsed imaging

Abstract: The application of terahertz pulsed imaging (TPI) in the in-line configuration to monitor the coating thickness distribution of pharmaceutical tablets has the potential to improve the performance and quality of the spray coating process. In this study, an in-line TPI method is used to measure coating thickness distributions on pre-coated tablets during mixing in a rotating pan, and compared with results obtained numerically using the discrete element method (DEM) combined with a ray-tracing technique. The hit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…To better understand the coating process and explain the observations, numerical simulation using DEM was suggested. As an initial step, the tablet coating process was simulated numerically [57], combined with a ray-tracing technique and validated against in-line TPI measurement of a pre-coated tablets during mixing in a rotating pan. Metrics of validation included the measurement rates and thickness distribution under increasing number of baffles in the mixing pan, where a good agreement was observed.…”
Section: In-line Measurementmentioning
confidence: 99%
“…To better understand the coating process and explain the observations, numerical simulation using DEM was suggested. As an initial step, the tablet coating process was simulated numerically [57], combined with a ray-tracing technique and validated against in-line TPI measurement of a pre-coated tablets during mixing in a rotating pan. Metrics of validation included the measurement rates and thickness distribution under increasing number of baffles in the mixing pan, where a good agreement was observed.…”
Section: In-line Measurementmentioning
confidence: 99%
“…From another study in 2018 of the same system, it was found that there were slight discrepancies between inline and o®line TPI measurement. 6 But such disagreement could be corrected by adjusting the measurement number per minute.…”
Section: Coatingmentioning
confidence: 99%
“…They are near-infrared (NIR) imaging, Raman imaging, terahertz pulsed imaging (TPI), ultraviolet (UV) imaging and Fourier transformed infrared (FT-IR) imaging. [2][3][4][5][6] NIR imaging and Raman seem to be the most used ones among them because of the deep spectral understanding and relatively low prices but each imaging technique has their own special expertise. Data fusion of various spectroscopy sources is therefore put forward such as the combination between NIR and Raman, or between visible and NIR (435-1042 nm) and short-wave infrared (898-1751 nm).…”
Section: Introductionmentioning
confidence: 99%
“…THz applications include security screening (García‐rial et al., ; Kaltenecker et al., ; (Liu, Zhong, Karpowicz, Chen, & Zhang, ), astronomical studies (Leisawitz et al., ), communication (Akyildiz, Miquel, & Han, ; Ergün & Sönmez, , nondestructive testing (Probst, Scheller, & Koch, ; Rutz, Koch, Khare, & Moneke, ), medical imaging (Bowman et al., ; Chavez, Bowman, Wu, Bailey, & El‐Shenawee, ; Dougherty et al., ; Fitzgerald et al., ; Sun et al., ; Truong, Fitzgerald, Fan, & Wallace, ), imaging of dental caries (Karagoz, Altan, & Kamburoglu, ; Ripoche, Reynard, Narcisse, & Roberts, ), pharmaceuticals (Markl, Dong, Li, & Zeitler, ; Pei et al., ; Sibik & Zeitler, ; Warnecke et al., , agricultural products (Liu et al., ; Liu, Liu, Hu, Yang, & Zheng, ; Luo, Zhu, Xu, & Cui, ; Nie, Qu, Lin, Dong, & He, ; Ogawa et al., ; Qin, Li, Chen, & Chen, ), food inspection and quality control (Ge, Jiang, Lian, & Zhang, ; Huang et al., , Shin, Choi, & Ok, ; Ok, Park, Kim, Chun, & Choi, ; Ok, Park, Lim, Jang, & Choi, ; Wang, Sun, & Pu, ; Yan, Liu, Qu, & Liu, ), environmental monitoring (Bigourd et al., ), and biosensing and label‐free monitoring of various biological processes (Yang et al., ). Full body THz scanners are installed in many airport checkpoints for detection of concealed objects and explosives.…”
Section: Introductionmentioning
confidence: 99%
“…. Narcisse, & Roberts, 2018), pharmaceuticals (Markl, Dong, Li, & Zeitler, 2018;Pei et al, 2018;Sibik & Zeitler, 2015;Warnecke et al, 2019, agricultural products (Liu et al, 2018Liu, Liu, Hu, Yang, & Zheng, 2016;Luo, Zhu, Xu, & Cui, 2019;Nie, Qu, Lin, Dong, & He, 2017;Ogawa et al, 2006;, food inspection and quality control Huang et al, 2015, Shin, Choi, & Ok, 2018Ok, Park, Kim, Chun, & Choi, 2014;Ok, Park, Lim, Jang, & Choi, 2018;Wang, Sun, & Pu, 2017;Yan, Liu, Qu, & Liu, 2018), environmental monitoring (Bigourd et al, 2006), and biosensing and label-free monitoring of various biological processes . Full body THz scanners are installed in many airport checkpoints for detection of concealed objects and explosives.…”
Section: Introductionmentioning
confidence: 99%